“Kd o pai dessa criança?!” : uma abordagem sociológica e comunicacional do discurso de atores sociais pais de crianças com síndrome de Down - Cunha, João Paulo Lima (2021)
Researches grounded on the assumptions of Critical Discourse Studies focus their analyses on a social problem that contains language as a determining factor. However, it is not only about being a problem, it is necessary that language is at the center of it to be an object of study. Thus, based on the monitoring of videos on the YouTube platform about what Down Syndrome (SD) is, we found that several comments questioned the practice of paternity. Therefore, since I am the father of a girl with DS, we reflect on the different social roles that are played by parents. We are still wondering about how the speeches legitimate relationships of abuse of power, affecting the social well-being of children with DS. This prompted us to try to comprehend how the parents were being represented in the speech. As a consequence, we built a critical, transdisciplinary enterprise, with an interpretive qualitative basis, based on the Sociological and Communicational Approach to Discourse (PEDROSA, 2014, 2016), which associated the Studies on Identities of Bajoit (2006; 2008; 2009b) with studies on the Halliday's Transitivity System (2004). That being so, we built the objective of understanding the multiple representations of the social actors, parents of children with DS, operationalized by the ideological evaluation system, concretized in the media space of video comments on YouTube, through the theoretical association between the identity spheres and verbal processes. In this perspective, we defend the thesis that the social actor is constituted by the identity sphere (attributed, desired and committed) and represented linguistically-discursively by verbal processes: do, be, feel, say, exist and behave. Moreover, to be an actor is to be a response to the different structural tensions and relationships established in social practices; also having the ability to question your tensions (BAJOIT, 2006; 2008; 2009b; PEDROSA, 2014; 2016). To develop this thesis, we observed 1,163 comments, present in eight videos, posted on YouTube, which dealt with SD. Therefore, we selected 150 comments that used semantic mentions of paternity to compose the body of the analysis. As a result, we verified three categories of actors (actors of assigned identity, desired identity and compromised identity) who represent themselves linguistically-discursively by doing, feeling, being, existing, saying and behaving. These representations are operationalized by the ideological evaluation system, instantiated socio-cognitively by the relations of abuse of power (VAN DIJK, 1997; 2008; 2012), expressing sexist, stereotyped discourses (DESCHAMPS; MOLINER, 2009), naturalized (FAIRCLOUGH, 2008; VIEIRA, 2017) and with asymmetric power relations (THOMPSON, 2002; DIJK, 2008). We also found commodified speeches (FAIRCLOUGH, 2008), colonized (RESENDE, 2019) and glamorized (SIFUENTES, 2017; 2018), both in relation to the father and in relation to people with DS. The research allows us to indicate the need for social change concerning the issue. Under these circumstances, we propose literacy practices, “discursive acquisition”, influencing future actions of the actors - through advertising, laws, training courses and 'mastery' of social networks, in order to propose discursive control, in an effective contribution for awareness and critical reflexivity (GIDDENS, 1991; BAJOIT, 2006) of those involved with the context of people with DS. Finally, our thesis contributes to the theoretical and methodological evolution of the Sociological and Communicational Approach to Discourse, as proposed by Critical Discourse Studies.